2013
DOI: 10.1007/s10067-013-2328-x
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing polychondritis: a review

Abstract: Relapsing polychondritis is a rare multisystem disease involving the cartilaginous and proteoglycan rich structures. The spectrum of clinical presentations may vary from intermittent episodes of painful and often disfiguring auricular and nasal chondritis, to occasional organ or even lifethreatening manifestations like airway collapse. There is lack of awareness about this disease due to its rarity. Relapsing polychondritis disease activity index has recently been validated and may help in clinical decision ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
99
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 96 publications
(110 reference statements)
2
99
0
1
Order By: Relevance
“…Due to the inflammation in the cartilaginous portion of the pinna, pain, discoloration, or tenderness in this area is frequently seen as the initial symptom. As in our patient, after repeated attacks, the cartilaginous structure of the ear is damaged and assumes a nodular or verrucous appearance, loses shape, and becomes soft and flabby (1,3). Symptoms of vestibular dysfunction, as well as impaired hearing, occasionally occur.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Due to the inflammation in the cartilaginous portion of the pinna, pain, discoloration, or tenderness in this area is frequently seen as the initial symptom. As in our patient, after repeated attacks, the cartilaginous structure of the ear is damaged and assumes a nodular or verrucous appearance, loses shape, and becomes soft and flabby (1,3). Symptoms of vestibular dysfunction, as well as impaired hearing, occasionally occur.…”
Section: Discussionsupporting
confidence: 49%
“…With this case presentation, our goal was to draw attention to this disease, which could be delayed for the diagnosis. Keywords: Arthritis, chondritis, relapsing polychondritis onset is the fifth decade of life, though cases have been reported in both extremes (3). Despite its unknown etiology, the pathogenesis seems to be an immunologic reaction to type II collagen, and studies have shown the association of both cellular immunity changes and abnormal autoantibody response in RP (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In RP, both specific T-cell clones responding to cartilage proteoglycans and circulating antibodies that denature type II and IV collagens are suspicious pathologic mechanisms of RP. RP with systemic vasculitis can be represented in 25 to 35% of the RP patients, involving cardiovascular, renal, skin and nerve vasculature [1]. We cannot give an explicit explanation as to why PI occurs in RP patients, however, considering many reported cases of PI with other connective tissue disorders, systemic vasculitis in RP might induce PI in those patients.…”
Section: Discussionmentioning
confidence: 91%
“…Relapsing polychondritis (RP) involves recurrently and progressively proteoglycan-rich organs and was first described in 1923 as "Polychondropathia" [1]. Yun et al reported first RP case in Korea [2].…”
Section: Introductionmentioning
confidence: 99%